2017
DOI: 10.1371/journal.pone.0187761
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of rotavirus vaccine (RotarixTM) in infants with environmental enteric dysfunction

Abstract: IntroductionDeployment of rotavirus vaccines has contributed to significant declines in diarrheal morbidity and mortality globally. Unfortunately, vaccine performance in low-middle income countries (LMICs) is generally lower than in developed countries. The cause for this has been associated with several host and maternal factors including poor water sanitation and hygiene (WASH) status, which are predominant in LMICs. More recently, environmental enteric dysfunction (EED) has specifically been hypothesized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
1
17
1
1
Order By: Relevance
“…In southern India, neither EndoCAb nor sCD14 were associated with OPV3 seroconversion or shedding [ 52 ]. The same was true in a Zambian study, where no association was seen for either EndoCAb or sCD14 and seroconversion to RVV [ 55 ].…”
Section: Results Overviewsupporting
confidence: 56%
See 3 more Smart Citations
“…In southern India, neither EndoCAb nor sCD14 were associated with OPV3 seroconversion or shedding [ 52 ]. The same was true in a Zambian study, where no association was seen for either EndoCAb or sCD14 and seroconversion to RVV [ 55 ].…”
Section: Results Overviewsupporting
confidence: 56%
“…Four of the eight studies reported overall a negative association between EED and oral vaccine responses, with elevated markers of EED associated with reduced oral vaccine performance [ 51 , 53 , 54 , 56 ]. Two studies showed no significant association [ 16 , 52 ] and two studies concluded that EED was positively correlated with immunogenicity to oral vaccine antigens [ 55 , 57 ]. The majority of studies relied on vaccine immunogenicity as a proxy for oral vaccine efficacy.…”
Section: Results Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Various factors have been postulated as contributing to this observed effect. Host factors such as genetics, malnutrition, enteric environmental dysfunction (EED), maternal factors such as antibodies passed onto the infant, various components of breast milk, exposure to HIV and other environmental factors including poor sanitation, concurrent infection with other pathogens have all been postulated to influence vaccine effectiveness [86][87][88][89][90][91][92][93][94][95][96][97].…”
Section: Improved Vaccine Effectiveness: Terrain à Fortementioning
confidence: 99%